Who should consent for research in adult intensive care? Preferences of patients and their relatives: a pilot study - Chenaud, C. (Journal of medical ethics, 2009)
Introduction: Research in intensive care is necessary for the continuing advancement of patient care. In research, informed consent is considered essential for patient protection. In intensive care, the modalities of informed consent are currently being debated by both lawyers and the medical community. The preferences of patients and their relatives regarding informed consent for research in intensive care have never been assessed. The aim of this study was to investigate these preferences.Methods: A pilot study conducted via a questionnaire mailed to patients and relatives who had experienced intensive care.Results: 52/400 patient-relative pairs completed the questionnaire fully. If the patient was imagined to be conscious, 75% of patients and 77% of relatives believed the patient should be the person who should consent. If the patient was imagined to be unconscious, 72% of patients and 67% of relatives thought that a relative should be asked to consent. The majority of responders thought that at least two persons should consent. Their answers were concordant in 61-80% of cases, depending on the question. Patients (25%) and relatives (30%) did not feel free in their decision to participate in a study. The majority of patients and relatives wanted to consent by writing, indifferently with or without a witness.Conclusion: Patients are willing to decide on their own participation in a study. If they lose their capacity to decide for themselves, in the great majority of cases, they would agree to delegate the decision to a relative.